Global comparison of University food services. - Lee, Sock Hwee. (2008)
The research project investigated the differences in operational characteristics of the universities' food services in selected countries of Australia, Canada, United Kingdom and the United States. Objective was to analyze the variables affecting such differences and to provide recommendations to improve the food services in Nanyang Technological University.